2003
DOI: 10.1074/jbc.m302895200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Responsible for Catalysis of the Inhibition of Factor Xa or Thrombin by Antithrombin Using a Covalent Antithrombin-Heparin Complex

Abstract: Covalent antithrombin-heparin (ATH) complexes, formed spontaneously between antithrombin (AT) and unfractionated standard heparin (H), have a potent ability to catalyze the inhibition of factor Xa (or thrombin) by added AT. Although Ϸ30% of ATH molecules contain two AT-binding sites on their heparin chains, the secondary site does not solely account for the increased activity of ATH. We studied the possibility that all pentasaccharide AT-binding sequences in ATH may catalyze factor Xa inhibition. Chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…ATH was analysed for purity using SDSPAGE under reducing conditions and was found to be 495% pure (21). We have previously shown that the AT content (amino acid analysis) and heparin content (by three different mass analysis methods) of ATH preparations are in a mole ratio of 1:1 (27).…”
Section: Preparation Of Athmentioning
confidence: 99%
“…ATH was analysed for purity using SDSPAGE under reducing conditions and was found to be 495% pure (21). We have previously shown that the AT content (amino acid analysis) and heparin content (by three different mass analysis methods) of ATH preparations are in a mole ratio of 1:1 (27).…”
Section: Preparation Of Athmentioning
confidence: 99%
“…Certainly, the existence of electric field differences between the endothelial lining and flowing blood has been previously recognized. 53 When insufficient PF4 is released, cell surfaces may retain sufficient negative charges to prevent optimal approximation of platelets and endothelial cells. Conversely, release of excessive amounts of PF4 may cause cell surfaces to become too positively charged for optimal cell-cell approximation.…”
mentioning
confidence: 99%
“…Application of large heparin dosing (usually 300-400 U/kg) and additional boluses to maintain suitable ACT response during CPB can potentially lead to bleeding complications during and after surgery. 18,34 We prepared a covalent ATH complex that exhibits increased plasma half-life, 20,28 decreased nonselective plasma/endothelial surface protein binding, 23 high catalytic inhibition of thrombin due to high activating pentasaccharide content, 20,21,35 and rapid neutralization of fibrinbound thrombin 26,27 relative to heparin. These features suggested that ATH may be an improved medication for reduction of arterial HITS as a possible surrogate measure of emboli during CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Covalent linkage of heparin to AT in the ATH complex allows the AT moiety to be in a permanently activated state. This is evident since the AT cannot dissociate from heparin 35 and the rate-limiting step of AT binding to heparin is eliminated. All ATH molecules have been shown to have at least one pentasaccharide sequence on the heparin chain to activate AT, and as many as 40% of the molecules possess 2 or more pentasaccharide sequences.…”
Section: Discussionmentioning
confidence: 99%